Evaluation of the policy program for strengthening local food commodities for sustainable food security in papua - Septinus Saa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Achieving sustainable food security in Papua remains a significant challenge due to the region's heavy reliance on imported food. The policy program aimed at bolstering local food commodities is designed to promote self-sufficiency and ensure long-term food sustainability. This study evaluates the policy program focused on strengthening local food commodities in Papua, specifically targeting sago, sweet potatoes, and maize. The objective is to assess the program's effectiveness in boosting local food production and its overall contribution to sustainable food security. The research methodology integrates both qualitative and quantitative approaches, incorporating secondary data analysis from government reports, field surveys of local farmers, and in-depth interviews with key stakeholders to gain a holistic perspective. The data analysis techniques included thematic analysis for qualitative data, ensuring detailed insights, and statistical methods for quantitative data to provide robust findings. The results indicate that the policy program has increased local food commodity production by 30% over the past five years. However, significant challenges remain, including inadequate infrastructure, limited market access, and insufficient support services for farmers, which hinder the full optimization of the program's benefits. The policy initiative has positively impacted food production and sustainable food security in Papua. For long-term success, it is crucial to improve infrastructure, expand market access, and provide continuous support and training for local farmers. This will ensure the gains achieved by the policy program are maintained and further developed, leading to a more resilient local food system in Papua